Are material ESG issues making their way into key audit matters? An analysis of Colombian innovative companies - Viviana Patricia Narváez-Castillo; María Antonia García-Benau; Laura Sierra-García; Nicolás Gambetta (Journal of Innovation & Knowledge)
This study examines whether auditors are innovating in their audit reports by incorporating material environmental, social, and governance (ESG) issues from companies' sustainability reports into the Key Audit Matters (KAMs) section. Additionally, it assesses whether ESG performance influences this inclusion. Content analysis was conducted on the materiality matrices of sustainability reports and KAMs disclosures for 20 Colombian companies listed on the COLCAP index during the period 2019–2021. Using logistic regression analysis, we examined relationships between ESG scores and KAMs disclosure of material ESG issues. The results obtained show that auditors strongly emphasise governance but tend to overlook social and environmental issues within their KAMs. Furthermore, higher governance scores increase the likelihood of ESG consideration in the KAMs, while lower profitability and leverage also lead to greater ESG inclusion in the KAMs. This pioneering study offers an initial analysis of whether material ESG issues arising from sustainability reports also appear in KAMs disclosures, thus addressing a significant literature gap. The study findings suggest that auditors need appropriate guidance and enhanced competencies to perform holistic ESG risk evaluation, as the acceptance of integrated sustainability reporting is gaining momentum globally.